Cements, Waters, and Scales: An Integrated Study of the Szeged Geothermal Systems (SE Hungary) to Characterize Natural Environmental Conditions of the Thermal Aquifer. (24th April 2019) - Varga, Andrea; Bozsó, Gábor; Garaguly, István; Raucsik, Béla; Bencsik, Attila; Kóbor, Balázs
Abstract : The study area, Pannonian Basin (Central Europe), is characterized by high heat flow and presence of low-enthalpy geothermal waters. In the Szeged Geothermal Systems (Hungary), having Miocene to Pliocene sandstone aquifers with dominantly Na–HCO3 -type thermal water, unwanted carbonate scaling was observed. An integrated approach consisting of host rock and scale mineralogical and petrographic analyses as well as water chemistry led to a better understanding of the characteristic natural (geogenic) environmental conditions of the geothermal aquifers and to highlight their technical importance. Analyses of the reservoir sandstones showed that they are mineralogically immature mixed carbonate-siliciclastic rocks with significant macroporosity. Detrital carbonate grains such as dolomite and limestone fragments appear as important framework components (up to ~20–25%). During water–rock interactions, they could serve as a potential source of the calcium and bicarbonate ions, contributing to the elevated scaling potential. Therefore, this sandstone aquifer cannot be considered as a conventional siliciclastic reservoir. In mudrocks, a significant amount of organic matter also occurs, triggering CO2 producing reactions. Correspondingly, framboidal pyrite and ferroan calcite are the main cement minerals in all of the studied sandstone samples which can suggest that calcite saturation state of the thermal fluid is close to equilibrium in oxygen-depleted pore water. Analysis of the dominant carbonate crystals in the scale can suggest that growth of the feather dendrites of low-Mg calcite was probably driven by rapid CO2 degassing of CO2 -rich thermal water under far-from-equilibrium conditions. Based on hydrogeochemical data and related indices for scaling and corrosion ability, the produced bicarbonate-rich (up to 3180 mg/l) thermal water has a significant potential for carbonate scaling which supports the aforementioned statement. Taking into consideration our present knowledge of geological setting of the studied geothermal systems, temporal changes in chemical composition and temperature of the thermal water during the heating period can indicate upwelling fluids from a deep aquifer. Regarding the pre-Neogene basement, hydrologic contact with a Triassic carbonate aquifer might be reflected in the observed chemical features such as decreased total dissolved solids and increased bicarbonate content with high scale-forming ability. The proposed upflow of basin-derived water could be channeled by Neogene to Quaternary fault zones, including compaction effects creating fault systems above the elevated basement high. The results may help to understand the cause of the high carbonate scale precipitation rates in geothermal systems tapping sandstone aquifers.